Consistencia de indicadores de especialización en el comercio internacional: Plicación al caso de la mantequilla en Argentina y Uruguay - Edith Depetris Guiguet; Rodrigo García Arancibia; Gustavo Rossini (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2010)
– This study aims to evaluate, in terms of their cardinal, ordinal, and dichotomy consistency, five alternative comercial specialization indicators: a Balassa symmetric index version; a Chi-Squared Index; and the Relative Trade Advantage Index, all these three based on revealed comparative advantage theory; and two additional: Michaely Index variation, and Iapadre Index variation, based on trade balance flows. It is applied to the particular case of Argentina and Uruguay butter world trade during 1995-2006. The results vary for both countries. Some indicators are found to be useful as substitutes while other in a complementary manner. Economically, the indicators show that the Argentine specialization fluctuates among years while the Uruguayan is very stable.
Keywords: F14; F15; C43; 330; Mercosur; trade flows; dairy products; indices of trade specialization; Internationale Arbeitsteilung; Streichfett; Außenhandel; Argentinien; Uruguay